2015
DOI: 10.3945/jn.115.212019
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Dietary Patterns during the Second Trimester Are Associated with Preterm Birth

Abstract: Diet quality during pregnancy is associated with preterm birth; thus, preconceptional and early prenatal dietary counseling promoting healthy dietary intake could improve pregnancy outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
116
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(132 citation statements)
references
References 34 publications
7
116
1
2
Order By: Relevance
“…Although greater adherence to the DASH (21) and Mediterranean (18) diets has been associated with a lower incidence of preterm birth, several studies observed no association (13,15,16,19). For birth size, a better-quality diet during pregnancy has generally been associated with higher birth weight (10,14,17) and a lower risk of fetal growth restriction (10,14,20), but other studies have reported no association (9,(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…Although greater adherence to the DASH (21) and Mediterranean (18) diets has been associated with a lower incidence of preterm birth, several studies observed no association (13,15,16,19). For birth size, a better-quality diet during pregnancy has generally been associated with higher birth weight (10,14,17) and a lower risk of fetal growth restriction (10,14,20), but other studies have reported no association (9,(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 89%
“…Existing studies have been conducted in white subjects (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) and no study, to our knowledge, has examined the association between maternal diet quality and infant birth outcomes in Asians. Furthermore, only one study examined the association between maternal diet quality and infant body composition by using air displacement plethysmography (9); and to our knowledge, no study to date has explored abdominal adiposity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Suboptimal maternal dietary intake during pregnancy is associated with adverse pregnancy outcomes, including gestational diabetes and hypertension 6 , and poorer birth outcomes. 7 Evidence suggests that improving prenatal F&V intake can promote optimal pregnancy and birth outcomes. Higher maternal F&V intake before or during pregnancy is associated with a decreased risk of miscarriage 8 , pre-eclampsia 9, 10 , upper respiratory infections 11 , and protects against gestational diabetes 12 in the mother.…”
Section: Introductionmentioning
confidence: 99%